The effect of viewing angle on observations of foot orientation in forensic gait analysis. Issue 6 (November 2020) - Reidy, Selina; Stephenson, John; Smith, Francine; Otten, Egbert; Wiedemeijer, Mickey; Curran, Mike
Highlights: Viewing angles used in forensic gait analysis can influence perceived foot angle. The most reliable view was in the frontal plane, from the back of the figure. The most unreliable view was obliquely, from the front and side of the figure. More accurate judgements were made about the foot situated closer to the camera.